Radiological Evaluation of TATE Elbow Cartridge Position in Dogs - Nutt, Anna E.; Shaw, Thomas A.; Knowles, Toby G.; Burton, Neil J. (Veterinary and Comparative Orthopaedics and Traumatology, 2018)
Objective The main purpose of this study was to evaluate the effect of varying elbow flexion angle and elbow orientation on the radiological measurement of component position for first (1G) and second-generation (2G) TATE elbow cartridges, and to test intra/inter-observer variability of measurements.Materials and Methods A cadaveric thoracic limb was implanted with a 1G then 2G cartridge, and mounted in lateral recumbency on an acrylic platform. The platform was tilted by set increments up to 10° in both planes, and radiographs were performed at each angle before repeating with the limb in caudocranial positioning. A deterministic trigonometric model was used to show how component angles should vary with changes in orientation, and these were compared with those measured by two observers. Humeral component angle (HCA), radioulnar component angle, varus/valgus cartridge alignment angle and the cartridge height:isthmus width ratio (CIR) were evaluated. Angles within 5° of the zero degrees inclination angle and ratios within 0.2 of the zero degrees inclination ratio were defined as acceptable.Results Observer component angles for both cartridges were accurate and precise for inclinations up to 10° except for HCA during adduction/abduction. The CIR values were within the acceptable limit for inclinations up to 7.5° in both planes.Clinical Significance Acceptable limits of limb inclination during positioning for TATE elbow replacement cartridge assessment were defined. All component measurements were sufficiently accurate and precise to be considered for evaluation of component position in clinical cases.
Keywords: canine total elbow replacement; TATE; component positioning; evaluation; radiological